Identification and characterization of a novel orbivirus, Yonaguni orbivirus, isolated from cattle on the westernmost island of Japan - Murota, Katsunori; Suda, Yuto; Shirafuji, Hiroaki; Ishii, Keiko; Katagiri, Yoshito; Suzuki, Moemi; Kobayashi, Daisuke; Isawa, Haruhiko; Tanaka, Shogo; Yanase, Tohru (Archives of Virology, 2020)
A novel orbivirus (genus Orbivirus , family Reoviridae ), designated Yonaguni orbivirus (YONOV), was isolated from bovine blood collected on a subtropical island of Japan in 2015. The YONOV genome (20,054 nucleotides in total) has a coding arrangement similar to those of mosquito-borne orbiviruses. YONOV has a close genetic relationship to mosquito-borne orbiviruses, especially to Mobuck virus (MBV), which was isolated in North America. However, YONOV and MBV share less than 74% nucleotide sequence identity in the major subcore protein (T2) coding sequence, which satisfies the criterion for species demarcation. It is still uncertain whether YONOV should be assigned to a novel species in the genus Orbivirus .